Desain dan Implementasi System Informasi Bank Data dan Penulisan Tugas Akhir Mahasiswa: (Studi Kasus Universitas Stella Maris Sumba) - Marden Bayo; Gergorius Kopong Pati; Emirensiana Dappa Ege (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Digital transformation in higher education requires an information system that is able to manage academic processes effectively, including the management of students' final projects. At Stella Maris University Sumba, the process of registering titles, guidance, and archiving of final projects is still carried out manually, causing various obstacles, such as administrative delays, difficulties in monitoring the progress of guidance, and the risk of data loss. This research aims to design and implement a web-based information system that supports the process of submitting titles, guidance management, uploading documents, and storing final project archives in the form of a digital data bank. The development method used is a software engineering approach with the stages of needs analysis, designing using UML, implementation, and system testing. The system is built with a three-layer architecture that features document management and role-based access control to ensure data security and integrity. The results of the black-box test showed that all system functions were running as needed, while the usability evaluation using the System Usability Scale (SUS) questionnaire resulted in a score that indicated the system was feasible to use. The implementation of this system has been proven to increase administrative efficiency, simplify the guidance process, and provide a structured thesis repository that supports academic transparency and accountability. Thus, this information system is expected to be a sustainable solution in the management of final projects as well as a model for the development of academic digitalization in higher education.